2008
DOI: 10.1158/1055-9965.epi-07-2780
|View full text |Cite
|
Sign up to set email alerts
|

Human Aflatoxin Albumin Adducts Quantitatively Compared by ELISA, HPLC with Fluorescence Detection, and HPLC with Isotope Dilution Mass Spectrometry

Abstract: Essential to the conduct of epidemiologic studies examining aflatoxin exposure and the risk of heptocellular carcinoma, impaired growth, and acute toxicity has been the development of quantitative biomarkers of exposure to aflatoxins, particularly aflatoxin B 1 . In this study, identical serum sample sets were analyzed for aflatoxin-albumin adducts by ELISA, high-performance liquid chromatography (HPLC) with fluorescence detection (HPLC-f), and HPLC with isotope dilution mass spectrometry (IDMS). The human sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 15 publications
6
65
1
Order By: Relevance
“…To address this data gap, a quantitative isotope dilution mass spec-trometry method was deployed to measure the aflatoxin B 1 -lysine albumin adduct at biologically critical times in mothers during pregnancy and in the first thousand days of life in their children. An initial analysis of aflatoxin-albumin adducts in a pooled sample from one thousand 6–7 year old children in Nepal found 56.5 pg aflatoxin B 1 -lysine/mg albumin, a level comparable to that detected in very nutritionally compromised children in West Africa when the different method of analyses are considered (Gong et al, 2004; McCoy et al, 2008). This biomarker observation prompted a more detailed examination using samples already analyzed for its plasma proteome that had collected during the first and third trimester of pregnancy of women enrolled in a randomized micronutrient intervention clinical trial in Sarlahi, Nepal (Cole et al, 2013; Scholl et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…To address this data gap, a quantitative isotope dilution mass spec-trometry method was deployed to measure the aflatoxin B 1 -lysine albumin adduct at biologically critical times in mothers during pregnancy and in the first thousand days of life in their children. An initial analysis of aflatoxin-albumin adducts in a pooled sample from one thousand 6–7 year old children in Nepal found 56.5 pg aflatoxin B 1 -lysine/mg albumin, a level comparable to that detected in very nutritionally compromised children in West Africa when the different method of analyses are considered (Gong et al, 2004; McCoy et al, 2008). This biomarker observation prompted a more detailed examination using samples already analyzed for its plasma proteome that had collected during the first and third trimester of pregnancy of women enrolled in a randomized micronutrient intervention clinical trial in Sarlahi, Nepal (Cole et al, 2013; Scholl et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…The development of mechanistically based biomarkers, such as the aflatoxin B 1 -lysine albumin adduct, has helped to overcome the inherent difficulties of assessing aflatoxin exposure by measuring dietary constituents. These biomarkers have the added advantage of being able to integrate exposures over the course of many weeks or months due to the long half-lives of these biomarkers in plasma (McCoy et al, 2005, 2008). Research from our laboratory has also demonstrated the long-term stability of aflatoxin albumin biomarkers in stored samples where we have found these adducts to be stable for up to 25 years (Scholl and Groopman, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although considerable success has been gained by measuring aflatoxin DNA and protein adducts using immunoassay methods, method development continues in this field, with the development of isotope dilution tandem mass spectrometry (IDMS) methods for detection of both urinary aflatoxin DNA adducts and serum albumin adducts (Egner et al, 2006;McCoy et al, 2008). Mass spectrometry provides higher specificity than other methods because the detection focuses on the signature fragmentation pattern of the aflatoxin adduct (Egner et al, 2006).…”
Section: Biomarkers Of Exposure For Aflatoxinmentioning
confidence: 99%
“…Analytical techniques such as thin-layer chromatography [6], high-performance liquid chromatography (HPLC) [7][8][9][10], and enzyme-linked immunosorbent assay (ELISA) have been available for the qualitative and quantitative analysis of AFB2 [11]. Although HPLC is the most commonly used method, because it offers high sensitivity and selectivity, it has some limitations in terms of costs incurred by the sophisticated equipment and the methods are not cost-effective, requiring a relatively long analysis time, so they are neither readily available in developing countries nor capable of on-site detection.…”
Section: Introductionmentioning
confidence: 99%